Methods for controlling and reporting resistance training proximity to failure: current issues and future directions - Pelland, J. C.; Robinson, Z. P.; Remmert, J. F.; Cerminaro, R. M.; Benitez, B.; John, T. A.; Helms, E. R.; Zourdos, M. C. (Sports Medicine, 2022)
Resistance training variables such as volume, load, and frequency are well defined. However, the variable proximity to failure does not have a consistent quantification method, despite being defined as the number of repetitions in reserve (RIR) upon completion of a resistance training set. Further, there is between-study variability in the definition of failure itself. Studies have defined failure as momentary (inability to complete the concentric phase despite maximal effort), volitional (self-termination), or have provided no working definition. Methods to quantify proximity to failure include percentage-based prescription, repetition maximum zone training, velocity loss, and self-reported RIR; each with positives and negatives. Specifically, applying percentage-based prescriptions across a group may lead to a wide range of per-set RIR owing to interindividual differences in repetitions performed at specific percentages of 1 repetition maximum. Velocity loss is an objective method; however, the relationship between velocity loss and RIR varies set-to-set, across loading ranges, and between exercises. Self-reported RIR is inherently individualized; however, its subjectivity can lead to inaccuracy. Further, many studies, regardless of quantification method, do not report RIR. Consequently, it is difficult to make specific recommendations for per-set proximity to failure to maximize hypertrophy and strength. Therefore, this review aims to discuss the strengths and weaknesses of the current proximity to failure quantification methods. Further, we propose future directions for researchers and practitioners to quantify proximity to failure, including implementation of absolute velocity stops using individual average concentric velocity/RIR relationships. Finally, we provide guidance for reporting self-reported RIR regardless of the quantification method.